Perampasan Hak dan Kesejahteraan Petani oleh Tengkulak di Kabupaten Aceh Barat - Rudi Andika; Marzuki Marzuki; Rahmad Halomoan Lubis; Cut Vely Muliyana; Safrida Safrida (Jurnal Public Policy, 2020)
Agriculture is one of the main centers as source of livelihood for the people  in west aceh  regency,  this  can  be  seen  from  the  yields  of farmers  which  are increasing  every  year.  However,  the  increase  in yields  is  inversely  proportional  to  the  welfare  of  the  west  aceh farmers,  due to the  influence of price manipulation by middlemen. This   study   aims   to   examine   the   role  and  supervision   of   the government  in protecting the rights of  farmers from middlemen in west Aceh district. The method used in this research is  qualitative with  a  variety  of  secondary  data  analysis   techniques   and  used scientific narrative review data analysis techniques. The results show that discrimination against farmer by middlemen was indeed common in west Aceh. The role of the west Aceh government in overcoming this problem is by providing education, issuing policies on program for providing business capital to farmers. Meanwhile, the supervision that the goverment faces is in the form of a minumun level of public response to policies that have been regulated by the government and a lack of trust from the peasant community in the government.